2015
DOI: 10.1002/2014ja020900
|View full text |Cite
|
Sign up to set email alerts
|

A prediction model for the global distribution of whistler chorus wave amplitude developed separately for two latitudinal zones

Abstract: Whistler mode chorus waves are considered to play a central role in accelerating and scattering electrons in the outer radiation belt. While in situ measurements are usually limited to the trajectories of a small number of satellites, rigorous theoretical modeling requires a global distribution of chorus wave characteristics. In the present work, by using a large database of chorus wave observations made on the Time History of Events and Macroscale Interactions during Substorms satellites for about 5 years, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 105 publications
1
12
1
Order By: Relevance
“…In Figure a, which represents the dayside magnetic field topology, we can see waves being locally generated in a broad range of high latitudes λ c >30° . Figures a–c show for the first time (in a self‐consistent, 2‐D simulation) the generation of wave power at higher latitudes on the dayside than at the nightside, in agreement with observational features discussed in section 1 [see, for example, results from Meredith et al , and Kim et al , ]. These results are consistent with maximum temperature anisotropy off equator and in line with the hypothesis put forward by Tsurutani and Smith [] that high‐latitude dayside chorus is produced at minimum B pockets caused by the solar wind compression of the Earth's magnetic field.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…In Figure a, which represents the dayside magnetic field topology, we can see waves being locally generated in a broad range of high latitudes λ c >30° . Figures a–c show for the first time (in a self‐consistent, 2‐D simulation) the generation of wave power at higher latitudes on the dayside than at the nightside, in agreement with observational features discussed in section 1 [see, for example, results from Meredith et al , and Kim et al , ]. These results are consistent with maximum temperature anisotropy off equator and in line with the hypothesis put forward by Tsurutani and Smith [] that high‐latitude dayside chorus is produced at minimum B pockets caused by the solar wind compression of the Earth's magnetic field.…”
Section: Resultssupporting
confidence: 88%
“…We show, for the first time, whistler-mode wave generation at high latitudes in the dayside and compare their characteristics to their dawn counterparts. The off-equatorial peak in whistler-mode wave power in the dayside, in contrast to an equatorial one in the nightside, is a salient feature of chorus observations [Meredith et al, 2003;Kim et al, 2015]. The results shown in this paper shed some light on a possible source mechanism that explains this contrasting difference.…”
Section: Introductionmentioning
confidence: 56%
See 1 more Smart Citation
“…Most statistical studies have grouped the observed chorus wave power into ranges of geomagnetic indices (AE/Kp) to differentiate between geomagnetic activity levels (Agapitov et al, 2013;Kim et al, 2015;Li et al, 2009;Meredith et al, 2001Meredith et al, , 2012. This grouping does not fully capture the transport history of electron drifts during storm times as they combine storm main and recovery phase effects.…”
Section: Introductionmentioning
confidence: 99%
“…An extension of this approach was employed by J.‐H. Kim et al [], who fit up to seventh‐order polynomials at every 2 h magnetic local time (MLT) interval to chorus wave intensity, in two latitude ranges and driven by either solar wind conditions or geomagnetic indices. While these functional fits make the models more flexible and dynamic, the functional forms used for fitting are only applicable to the parameter at hand and a new approach will inevitably need to be taken if a different parameter is to be predicted.…”
Section: Introductionmentioning
confidence: 99%